Prijungiamieji laiko sakiniai su ribos reikšmės jungiamaisiais žodžiais 16–17 a. lietuviškuose raštuose - Pajėdienė, Jūratė (Baltistica, 2011)
Subordinate clauses of time boundary in Old Lithuanian writings The article gives an overview of the structure and semantics of subordinate clauses of time boundary with conjunctions net, neg, kol, iki in Old Lithuanian writings (in texts of J. Bretkūnas’ Postilla (1591), M. Daukša’s Postilla (1599) and K. Sirvydas’ Punktai sakymų (I – 1629, II – 1644). The comparative analysis of the material shows that the temporal conjunction net has a peculiarity to fit semantically with one of the other conjunctions of time limit or boundary (iki, kol, neg). The closeness of meaning between the conjunctions net and iki, net and kol, net and negu depends on the grammatical structure of the complex sentence. Temporal clauses with conjunctions net have a fixed final clause order, clauses with iki are also often ( 88%) used in the final position. The temporal clauses introduced by conjunctions net, iki can include finite and / or non-finite verb forms. Temporal clauses with net and correlative word of duration taip ilgai show the closeness of meaning between the conjunctions net and kol. The tendency to change conjunction net to conjunction kol is seen in temporal clauses with the subjunctive. There is also a semantic similarity between temporal clauses with net (together with correlative word pirm) and temporal clauses with neg. Temporal clauses with compound conjunction pirm neg are most frequent in all these texts, temporal clauses introduced by single conjunction neg are identified in Daukša and Sirvydas. In most cases a correlation between clause order and iconicity is seen: 72% of grand total of subordinate clauses of time boundary used in Bretkūnas’, Daukša’s and Sirvydas’ writings are the posterior temporal clauses.